Shaving of the Plaster Working Dies Reusing the Final Silicone Impression. A Coupling Technique - Ramírez Barrantes, Juan Carlos (2022)
One of the most predominant challenges in oral rehabilitation is to predict the functional and aesthetic results of dental restorations. The success of the treatment depends on the correct execution of the different clinical and technical procedures performed at the dental laboratory. One of the fundamental steps is the final impression to obtain a precise replica of the cervical termination line. The correct diagnosis for the approach regarding the gingival tissues, the fidelity of the dental impression, and the shaving of the gingival margins in the working model will allow the establishment of a complete protocol for the diagnosis, planning, and execution of the treatment, potentiating more predictable results in the different clinical cases. The aim of this case report was to propose an alternative technique for undergraduate students regarding the shaving procedure of the working dies, obtaining an improved fitting in the marginal adaptation of the prosthetic parts performed at the laboratory.